Proximate composition and energetic value of selected marine fish and shellfish from the west coast of Peninsular Malaysia - Abd Aziz @ Mughni, Nurnadia; Azlan, Azrina; Ismail, Amin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
This study was conducted to determine the proximate composition and energetic value of selected marine fish and shellfish from the West Coast of Peninsular Malaysia. This study has included 20 species of fish (10 pelagic fish and 10 demersal fish) and 4 species of shellfish. For pelagic fish, Longtail shad (terubuk) was found to contain significantly lower moisture (59.31+0.00%), but significantly higher fat content (23.15+0.00%) compared to other fish species. For demersal fish, moisture and ash contents ranged between 74-82%, and 0.9-2.1%, respectively. Long-tailed butterfly ray contained the highest protein (22.22+1.24%) compared to other fish studied. The highest fat content of demersal fish was in Moonfish at 6.89+2.76%. For shellfish, prawn contained the highest protein (19.12+1.44%). The fat content of shellfish ranged between 1-2%. Oyster contained significantly higher carbohydrate at 6.45+0.00%, compared to other shellfish. Longtail shad contained the highest energetic value of 13.34 kJ g-1 of all samples. These values are useful references for consumers in order to choose fish and shellfish based on their nutritional contents.